Carbon Dots Evoked Li Ion Dynamics for Solid State Battery. Issue 39 (20th August 2021) - Xu, Laiqiang; Li, Jiayang; Li, Lin; Luo, Zheng; Xiang, Yinger; Deng, Weina; Zou, Guoqiang; Hou, Hongshuai; Ji, Xiaobo
Abstract: Solid composite electrolyte‐based Li battery is viewed as one of the most competitive system for the next generation batteries; however, it is still restricted by sluggish ion diffusion. Fast ion transport is a characteristic of the polyethylene oxide (PEO) amorphous phase, and the mobility of Li + is restrained by the coordination interaction within PEO and Li + . Herein, the design of applying functionalized carbon dots (CDs) with abundant surface features as fillers is proposed. High ionic conductivity is achieved in the CD‐based composite electrolytes resulting from enhanced ion migration ability of polymer segments and mobility of Li + . Specially, the optimum effect with nitrogen and sulfur co‐doped carbon dots (NS‐CD) is a consequence of strong interaction between edge‐nitrogen/sulfur in NS‐CD and Li + . Solid‐state nuclear magnetic resonance results confirm that more mobile Li + is generated. Moreover, it is observed that lithium dendrite is suppressed compared to PEO electrolyte associated with reinforced mechanical properties and high transference number. The corresponding all‐solid‐state batteries, with the cathode of LiFePO4 or high voltage NCM523, exhibit long cycling life and excellent rate performances. It is a novel strategy to achieve high ionic conductivity composite electrolyte with uniform lithium deposition and provides a new direction to the mechanism of fast Li + movement. Abstract : Functionalized carbon dots (CDs) are utilized to construct polyethylene oxide composite electrolytes with high ionic conductivity. Heteroatom within the surface of CDs will have interaction with Li +, affecting the ion movement in the composite electrolytes. A new direction for the selection of composite electrolyte and the mechanism of fast Li + movement are provided.